The Influence of Service Quality, Brand Image, and Digital Marketing on Purchasing Decisions - Azzahra, Fanisha Merinda (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This research is motivated by the high use of the Internet for various activities, such as communication, education, entertainment, and business. Three factors are considered to have a dominant influence on the development of the business sector, namely improving Service Quality, Brand Image, and Digital Marketing. This study aims to look at the effect of Service Quality, Brand Image, and Digital Marketing on Purchasing Decisions. The research was conducted at Karla Pet Shop. The research method used is descriptive verification research with a quantitative approach with a sample size of 150 people who have shopped for Karla Pet Shop products either directly or online. The sampling technique used is the purposive sampling technique. This research was conducted by distributing questionnaires, interviews, and observations as data collection techniques. Testing the questionnaire with validity test and reliability test. The analysis method uses classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that Service Quality, Brand Image, and Digital Marketing partially had a positive and significant effect on Purchasing Decisions. Meanwhile, the results of the study simultaneously show that Service Quality, Brand Image, and Digital Marketing have a positive and significant effect on Purchasing Decisions at Karla Pet Shop. Better Service Quality, good Brand Image, and appropriate Digital Marketing (good) increase Purchasing Decisions at Karla Pet Shop.